Erythrodermic mycosis fungoides and Sézary syndrome treated with extracorporeal photopheresis as part of a multimodality regimen: A single‐centre experience. (24th August 2015) - Atzmony, L.; Amitay‐Laish, I.; Gurion, R.; Shahal‐Zimra, Y.; Hodak, E.
Abstract: Background: Extracorporeal photopheresis (ECP) is recommended for the erythrodermic mycosis fungoides (MF) and Sezary syndrome (SS) alone or in combination with other therapies. The possibility of a differential response in the blood and skin has hardly been addressed in the literature. Objectives: To evaluate the clinical response rate of patients with erythrodermic MF and SS to ECP as part of a multimodality approach and to compare the kinetics of the blood and skin responses in the presence of leukaemic involvement. Methods: Twenty patients were treated with ECP and other modalities at a tertiary medical centre in 2003–2013. Ten patients had SS, 1 CD8‐positive patch‐stage MF with leukaemic involvement and nine erythrodermic MF. Clinical and outcome data were collected retrospectively from the medical files. Response was evaluated overall and for blood and skin separately. Results: Adjunctive therapies were interferon‐α, narrow‐band ultraviolet B, psoralen and ultraviolet A, isotretinoin, acitretin, methotrexate, prednisone, topical nitrogen mustard and total skin or localized hands/feet electron beam radiotherapy. Overall response was documented in 13 patients (65%) – complete 30%, partial 35% – and maintained for >2 years in 38.5%. In patients with leukaemic involvement ( n = 11), the blood response occurred earlier than skin response ( P = 0.008) and was maintained longer ( P = 0.03). In three of the patients with a complete blood response, the skin response was partial ( n = 2) or absent ( n = 1). Conclusion: Extracorporeal photopheresis as part of a multimodality approach yields a high durable clinical response in patients with erythrodremic MF and SS. The kinetics of the response differ between the blood and skin. The blood response occurs earlier and lasts longer; it does not necessarily predict the clinical skin response. Further studies are needed to determine if there is a survival advantage to a blood response in the absence of a skin response.